Pengaruh Promosi, Cash on Delivery, dan Viral Marketing Terhadap Keputusan Pembelian Pada Marketplace Shopee (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Jannah, Shofiratul; Mardani, Ronny Malavia; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Promotions, Cash on Delivery, and Viral Marketing on Purchasing Decisions in the Shopee marketplace. Type of survey research with a quantitative approach. The population in this study were Shopee application users who had made a purchase at Shopee at least once within the Islamic University of Malang. The sampling technique used purposive sampling with a sample of 75 respondents. Data was obtained from a questionnaire using a Likert scale. Analysis of this research data uses multiple linear regression analysis. This research contributes to knowing the factors that influence purchasing decisions on the Shopee marketplace. The results of this research are that Promotion, Cash on Delivery, and Viral Marketing partially influence purchasing decisions on the Shopee marketplace. Keywords: Purchasing Decisions, Promotion, Cash on Delivery,dan Viral Marketing